Da felicidade à alegria: os usos e as apropriações do telejornal Jornal Nacional por famílias de classe popular - Cechella, Tissiana Nogueira Pereira (2015)
This is a study of news reception carried out with three popular class families, which live in the Renascença Village, located at the West region of Santa Maria, in Rio Grande do Sul. The purpose of this research is to reflect about the uses and appropriations that these families do about the Jornal Nacional of Rede Globo de Televisão based on the communicative mediations of culture: sociability and rituality. For this, the theoretical axis of the research is Latin American Cultural Studies, mainly the Mediations Theory of Martín-Barbero (1987) and the social class concept of Pierre Boudieu (2006). The methodology of this study is a critical ethnography of reception, which was proposed by Ronsini (2010, p. 2). The results show that the uses and appropriations of news by the families are essentially determined by the social class which they belong as well as by their cultural, economic and social capitals. Furthermore, it is permeate by questions related with generation, because the news is important for the adults, which watch and appropriating of the messages daily, unlike the young that watch the news with low frequency and are interested in few reports of the news. The uses and appropriations also are related to gender, because, many times, is different for the men and women, beyond the domestic space and temporal configuration, which is mobilized in full during the television program exhibition. The mediations sociability and rituality are fundamental for the comprehension of the uses and appropriations of news because focus significantly on their configuration. The three investigated families elaborate their popular class representations based on their experience and their everyday, but also based on news, although they affirm that are not totally represented by the television program. The cultural capital of the three families is elaborated, primarily, by the media, mostly based on television (news and soap opera).